2019
DOI: 10.3389/fnins.2019.01020
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Analysis of Early Gene Expression Using Egr-1 Immunolabeling After Spreading Depression in the Rat Somatosensory Cortex

Abstract: Early growth response-1 (Egr-1), defined as a zinc finger transcription factor, is an upstream master switch of the inflammatory response, and its expression can be used to investigate the spatial and temporal extent of inflammatory changes in the brain. Cortical spreading depression (CSD) is characterized as a slowly propagating (2–5 mm/min) depolarization wave through neurons and astrocytes in humans that contributes to migraines and possibly to other brain pathologies. In rodents, CSD can be induced experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…After induction, spreading depression will travel along the longitudinal axis of the hippocampus and will not be induced in the contralateral hemisphere. It was previously shown that in the neocortex, spreading depression increases the expression of c-fos [ 32 ], arc [ 33 ], egr1 [ 34 ], npas4 [ 35 ], bdnf [ 33 ], il1b [ 36 ], and tnf [ 36 ]. Our data are in agreement with these observations because in our case, the expression of all these genes, except il1b , increased in the right ventral hippocampus compared to the left ventral hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…After induction, spreading depression will travel along the longitudinal axis of the hippocampus and will not be induced in the contralateral hemisphere. It was previously shown that in the neocortex, spreading depression increases the expression of c-fos [ 32 ], arc [ 33 ], egr1 [ 34 ], npas4 [ 35 ], bdnf [ 33 ], il1b [ 36 ], and tnf [ 36 ]. Our data are in agreement with these observations because in our case, the expression of all these genes, except il1b , increased in the right ventral hippocampus compared to the left ventral hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Egr1-enhanced green fluorescent protein (EGFP) transgenic mice were used to apply the endogenous fluorescent signal to indicate neural activity in the brain at cellular resolution (Xie et al, 2014). Previous study has demonstrated that cortical spreading depression (CSD), which might be involved in the biological process of migraine attack, up-regulated Egr1 expression in the somatosensory cortex (Sosthenes et al, 2019). However, there is no research on the expression of Egr1 in the whole brain of CM model.…”
Section: Introductionmentioning
confidence: 99%
“…At the transcriptomic level, several studies have confirmed that CSD modulates gene expression in the cerebral cortex of rodents. Specifically, CSD has been shown to modulate the expression of genes involved in inflammatory processes (30), in sleep homeostasis (31), in neuroprotection (32) and in stress responses (33), amongst others. In agreement with this, our group showed in a previous study that CSD induction in the same samples used in this study modulates the expression of genes related to hormone stimulus, apoptosis, synaptic transmission and interleukin signaling, without differences between the animals pre-treated or not with TPM or VPA (34).…”
Section: Discussionmentioning
confidence: 99%